Trade Facilitation and Export diversification in South Africa - Primo, Jessyca (School of Economics, 2019)
This paper uses a gravity model to investigate the impact of trade facilitation on export diversification in South Africa. This paper uses panel data of 124 countries ranging over the period 2012 – 2016. In this paper, a statistical approach called factor analysis was used to construct four new aggregate trade facilitation indicators from a wide range of primary indicators that measured many aspects of trade facilitation for each of the countries in the panel and the number of product lines exported from South Africa was used as a measure of export diversification. We include simple average import tariffs of each country, distance, GDP, population, geographical and cultural variables and regional trade agreements with South Africa. As our export diversification measure is discrete (i.e. count data), we postulate that the number of product lines exported to each country follows a Poisson distribution which follows the approach used by Dennis & Shepherd (2011) and Persson (2013). The focus of this paper is to determine the impact of on-the-border trade facilitation on export diversification. We find that border and transport efficiency contributes significantly to export diversification and the effect is confirmed when examining export diversification between countries. We also find that ocean ports, airports, custom procedures and number of days to import drive this contribution of border and transport efficiency on export diversification.